2022
DOI: 10.1101/2022.04.07.487323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structure of the F420-dependent sulfite-detoxifying enzyme from Methanococcales reveals a prototypical sulfite-reductase with assimilatory traits

Abstract: The coenzyme F420-dependent sulfite reductase (Fsr group I) protects hydrogenotrophic methanogens, one of the main contributors in worldwide methane emission, from toxic sulfite. Fsr is a single peptide composed of a F420H2-oxidase and a novel class of sulfite reductase. Both catalytic domains have been proposed to be the ancestors of modern F420-oxido/reductases and dissimilatory/assimilatory sulfite reductases. Here, we describe the X-ray crystal structures of Fsr natively isolated from Methanocaldococcus ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Series of incubations with different NH4Cl concentrations, ranging from 0.1 to 16.8 mM, showed that M. thermolithotrophicus required a minimum of 10 mM NH4Cl for best growth (Fig. 1A) in our optimized medium (see Materials and Methods for composition) (39,40).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Series of incubations with different NH4Cl concentrations, ranging from 0.1 to 16.8 mM, showed that M. thermolithotrophicus required a minimum of 10 mM NH4Cl for best growth (Fig. 1A) in our optimized medium (see Materials and Methods for composition) (39,40).…”
Section: Resultsmentioning
confidence: 96%
“…Series of incubations with different NH 4 Cl concentrations, ranging from 0.1 to 16.8 mM, showed that M. thermolithotrophicus required a minimum of 10 mM NH 4 Cl for best growth (Fig. 1A) in our optimized medium (see Materials and Methods for composition) (39, 40). Higher NH 4 Cl concentrations of 25-200 mM NH 4 Cl did not result in higher cell yields, and a 500 mM excess of NH 4 Cl led to a decrease (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations